2015
DOI: 10.4236/ad.2015.34012
|View full text |Cite
|
Sign up to set email alerts
|

Long-Distance Travel and Trading in the Bronze Age: The East Mediterranean-Scandinavia Case

Abstract: Bronze was imported to Scandinavia from the East Mediterranean. This trading started about 1750 BC. At just the same time amber from the Baltic started to appear in Mycenaean and Minoan graves. This gives evidence of active trading between the Mediterranean and Scandinavia. The sudden appearance of picture of large ships cut into bedrock surfaces and blocks at about the same time suggests that this trading took place via visitors arriving by ships. The size of the ships seems to preclude a stepwise transfer vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Significantly, amber started to occur in great quantities in Mycenaean and Minoan tombs from about 1600 BC Mörner & Lind, 2015). Three omega signs occur in southern Sweden (Mörner & Lind, 2015). Obviously, they must owe their origin to Ancient Greece.…”
Section: Sun Cult In Northern Europementioning
confidence: 99%
See 4 more Smart Citations
“…Significantly, amber started to occur in great quantities in Mycenaean and Minoan tombs from about 1600 BC Mörner & Lind, 2015). Three omega signs occur in southern Sweden (Mörner & Lind, 2015). Obviously, they must owe their origin to Ancient Greece.…”
Section: Sun Cult In Northern Europementioning
confidence: 99%
“…In a number of papers, we have shown that people from the Eastern Mediterranean region established a trading centre in southeast Sweden ( Figure 1, site 5) in about 1750 BC , 2013, 2015. They brought bronze into Sweden, initiating the Scandinavian Bronze Age (Mörner & Lind, 2015). The proposed trading centre in the Ravlunda-Kivik area is just where yellow amber was accessible in large quantities (Figure 1, site 5).…”
Section: Sun Cult In Northern Europementioning
confidence: 99%
See 3 more Smart Citations